Keabsahan Jual Beli Mystery Box Perspektif Pasal 1320 KUH Perdata - Ishakimuda Lawrensius Basaro; Adi Sulistiyono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article aims to find out the validity of a mystery box sale and purchase agreement from the perspective of article 1320 of the Civil Code. It is hoped that the results of this research can be used by parties, especially potential online loan recipients, in making an online loan agreement using a standard agreement system. The research methodology uses normative law, including primary and secondary legal documents, as well as data collection approaches such as literature reviews. A conceptual approach and a statutory approach were used in this research. The data analysis technique used was a deductive data analysis technique using the syllogism method. The validity of an agreement is assessed based on 4 main points of the validity of an agreement based on article 1320 of the Civil Code. Likewise, a sale and purchase agreement is considered valid according to law if it fulfills the 4 elements of the validity of an agreement